Mitochondria-targeting cyclometalated iridium(iii) complexes for tumor hypoxic imaging and therapy. Issue 4 (11th March 2019) - Li, Jia; Chen, Hongmin; Zeng, Leli; Rees, Thomas W.; Xiong, Kai; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract : The organometallic anthraquinone iridium(iii ) complexes display an efficient turn-on phosphorescence response to hypoxia. The complexes can induce cell apoptosis in HeLa cells via mitochondrial dysfunction and caspase-3 activation making them excellent candidates as theranostic agents for hypoxic cancer cells. Abstract : Hypoxia is frequently found in the center of solid tumors. It contributes to drug resistance and is a major obstacle in the development of effective cancer therapy. Designing activatable theranostic agents for hypoxic cancer cells remains a big challenge. We herein report five novel cyclometalated iridium(iii ) complexes with an attached anthraquinone moiety (Ir1–5 ) for hypoxic cancer cell therapy. The complexes efficiently respond to hypoxia with a turn-on yellow phosphorescence and were successfully used to detect hypoxia within 3D multicellular tumor spheroids. Moreover, the complexes are cytotoxic towards HeLa (human cervical carcinoma), HepG2 (Human hepatocellular carcinoma), A549 (human lung carcinoma), and A549R (cisplatin-resistant human lung carcinoma) cell lines, withIr2 more than 50 times as active as cisplatin against the A549R cell line. Investigation of the localization ofIr1–5 indicates that mitochondria are the main cellular targets. Mitochondrial dysfunction and caspase-3 activation were found to be involved in the apoptotic cell death pathway induced by the complexes. These results demonstrate that the complexes have great potential for tumor diagnosis and therapy in the future.